Quantum dot color conversion film resistant to high blue light radiation and high temperature and preparation method thereof
By growing the ZnS shell on the surface of Zn-In/La-S quantum dots and covering the polydopamine layer, combined with graphene oxide-coated ZnCNi3, a quantum dot color conversion film that is resistant to high blue light radiation and high temperature resistant is produced, solving the problem of poor performance in the prior art and achieving efficient spectral conversion and stable performance.
Patent Information
- Application Number
- CN202411932884.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing fluorescent high-blue radiation and high-temperature resistant quantum dot color conversion films do not have high-blue radiation and high-temperature resistant properties, which limits its application.
By preparing Zn-In/La-S quantum dots, and after growing the ZnS shell on its surface, the polydopamine layer was coated, combined with graphene oxide-coated ZnCNi3, and evenly spin-coated on the polycarbonate film, a quantum dot color conversion film that is resistant to high blue light radiation and high temperature resistance is produced.
It significantly improves the luminous intensity and stability of quantum dots, enhances its barrier efficiency to ultraviolet and blue light, has better heat, oxygen and chemical stability, and is suitable for a wide range of applications.
Smart Images

Figure BDA0005210787610000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of color conversion films, and in particular to a quantum dot color conversion film resistant to high blue light radiation and high temperature and a preparation method thereof. Background Art
[0002] Fluorescent quantum dot color conversion film with high blue light radiation resistance and high temperature resistance is a special material that can convert light of a specific wavelength into light of other wavelengths, and is usually used to improve light efficiency and change the spectral distribution of light. Organic / inorganic composite quantum dot color conversion film with high blue light radiation resistance and high temperature resistance is prepared by uniformly dispersing organic fluorescent pigments and inorganic phosphors in a certain proportion into a specific matrix. For example, organic fluorescent pigment VQ-D25 and inorganic phosphor yttrium aluminum garnet (YAG) can be uniformly dispersed in PMMA, and a fluorescent quantum dot color conversion film with high blue light radiation resistance and high temperature resistance is formed by coating and curing.
[0003] A method for preparing a fluorescent quantum dot color conversion film that is resistant to high blue light radiation and high temperature involves mixing a rare earth compound, urea and water to obtain a rare earth source solution, and then preparing a fluorescent quantum dot color conversion film that is resistant to high blue light radiation and high temperature through steps such as homogeneous precipitation and heat treatment. This method uses rare earth elements and urea, first prepares a precursor film through a hydrothermal method, and then prepares a fluorescent quantum dot color conversion film that is resistant to high blue light radiation and high temperature through heat treatment. The method has simple steps, convenient operation, and a short preparation cycle. However, this type of fluorescent quantum dot color conversion film that is resistant to high blue light radiation and high temperature does not have the performance of being resistant to high blue light radiation and high temperature, which greatly limits its application. Summary of the invention
[0004] The purpose of the present invention is to propose a quantum dot color conversion film that is resistant to high blue light radiation and high temperature and a preparation method thereof, which has good resistance to high blue light radiation and high temperature, high efficiency in blocking ultraviolet light and blue light, low cost, good heat resistance and chemical stability, can withstand water and oxygen environments, and has broad application prospects.
[0005] The technical solution of the present invention is achieved in this way:
[0006] The invention provides a method for preparing a quantum dot color conversion film resistant to high blue light radiation and high temperature. Zn-In / La-S quantum dots are prepared, a ZnS shell is grown on the surface, and then a polydopamine layer is coated to obtain modified Zn-In / La-S quantum dots coated with the ZnS shell, which are mixed with graphene oxide-coated ZnCNi3 in a solvent, and are evenly spin-coated on a polycarbonate film. The other side is treated in the same way and dried to obtain a quantum dot color conversion film resistant to high blue light radiation and high temperature.
[0007] As a further improvement of the present invention, the following steps are included:
[0008] S1. Preparation of Zn-In / La-S quantum dots: zinc acetate, indium acetate, lanthanum acetate, sulfur powder, oleylamine and thiol were mixed, heated for reaction under the protection of inert gas, and cooled to room temperature to obtain a Zn-In / La-S quantum dot reaction solution;
[0009] S2. Coating with ZnS shell: dissolving zinc acetate in oleylamine and octadecene solution, adding to the Zn-In / La-S quantum dot reaction solution in step S1, heating the reaction, cooling to room temperature, purifying with methanol, centrifuging, and obtaining Zn-In / La-S quantum dots coated with ZnS shell;
[0010] S3. Polydopamine coated layer: Add Zn-In / La-S quantum dots coated with ZnS shell into water, add dopamine hydrochloride and catalyst, heat and stir to react, centrifuge, wash, and dry to obtain modified Zn-In / La-S quantum dots coated with ZnS shell;
[0011] S4. Preparation of ZnCNi3: ZnO and NiO are mixed, melamine is added, stirred and mixed evenly, and calcined to obtain ZnCNi3;
[0012] S5. Graphene oxide coating: adding graphene oxide to water, adding ZnCNi3, ultrasonically dispersing uniformly, spray drying, to obtain graphene oxide coated ZnCNi3;
[0013] S6. Preparation of the suspension: The modified Zn-In / La-S quantum dots coated with ZnS shell and graphene oxide coated ZnCNi3 were added to the solvent and stirred to mix well to obtain a suspension;
[0014] S7. Preparation of quantum dot color conversion film resistant to high blue light radiation and high temperature: evenly spin-coat the suspension on a polycarbonate film, treat the other side in the same way, and dry to obtain a quantum dot color conversion film resistant to high blue light radiation and high temperature.
[0015] As a further improvement of the present invention, the mass ratio of zinc acetate, indium acetate, lanthanum acetate, sulfur powder, oleylamine and mercaptan in step S1 is 3-4:5-7:2-3:6-8:400-700:300-500, the temperature of the heating reaction is 220-240°C, and the time is 10-15 min.
[0016] As a further improvement of the present invention, the mass ratio of zinc acetate, oleylamine and octadecene solution, and Zn-In / La-S quantum dot reaction solution in step S2 is 7-10:100:1000-1200, the temperature of the heating reaction is 240-250°C, and the time is 20-30min.
[0017] As a further improvement of the present invention, the mass ratio of the Zn-In / La-S quantum dots coated with the ZnS shell, dopamine hydrochloride and the catalyst in step S3 is 10:2-3:0.1-0.2, the pH of the catalyst is Tris-HCl solution of 8.5-9.5, the temperature of the heating and stirring reaction is 35-45°C, and the time is 3-5h.
[0018] As a further improvement of the present invention, in step S4, the molar ratio of ZnO, NiO and melamine is 1:2-4:4-6, the calcination temperature is 550-650° C., and the calcination time is 10-14 h.
[0019] As a further improvement of the present invention, the mass ratio of graphene oxide to ZnCNi3 in step S5 is 3-5:10.
[0020] As a further improvement of the present invention, the mass ratio of the modified Zn-In / La-S quantum dots coated with ZnS shells, graphene oxide coated ZnCNi3 and the solvent in step S6 is 7-10:3-5:100-200, and the solvent is at least one of n-octane, n-hexane, cyclohexane and petroleum ether.
[0021] As a further improvement of the present invention, the rotation speed of the spin coating in step S7 is 2500-3500 r / min, and the time is 40-50 s.
[0022] The present invention further protects a quantum dot color conversion film which is resistant to high blue light radiation and high temperature and is prepared by the above-mentioned preparation method.
[0023] The present invention has the following beneficial effects:
[0024] Quantum dots are highly favored in wide color gamut displays due to their high luminous efficiency and narrow line width. However, they are easily affected by water, heat and oxygen, resulting in a decrease in luminous efficiency. The present invention uses a ZnS shell layer grown on the surface of Zn-In / La-S quantum dots to increase the luminous intensity of quantum dots while significantly improving their heat and oxygen resistance, effectively protecting the core quantum dots from erosion by the external environment, significantly improving their stability, and significantly enhancing the luminous efficiency of quantum dots through the effective restriction of photogenerated carriers by the shell material.
[0025] The quantum dots of the present invention are doped with indium and lanthanum elements. The doping with lanthanum elements can improve the fluorescence performance and thermal stability thereof. Because of its large Stokes shift, the self-quenching phenomenon caused by self-absorption can be well avoided, and the thermal stability, chemical stability and longer fluorescence life of the quantum dots are greatly improved. The doping with indium elements significantly reduces the disorder inside the organic semiconductor layer, and can have a significant effect on the structure, morphology and size of the quantum dots, so that the size of the quantum dots is significantly reduced, and the quantum dots have good ultraviolet and blue light blocking efficiency. The quantum dots prepared by the two have better temperature resistance, blue light blocking, thermal stability and chemical stability, and have a synergistic effect.
[0026] The surface of the Zn-In / La-S quantum dots coated with the ZnS shell prepared by the present invention is further protected by a polydopamine layer, which further improves the chemical stability and fluorescence stability of the quantum dots, reduces the transmission barrier between the quantum dots, improves the carrier mobility, enhances the optical properties of the quantum dots, and improves the adhesion of the quantum dots to the graphene oxide-coated ZnCNi3 and the adhesion on the polycarbonate film.
[0027] ZnCNi3 has an antiperovskite structure, which has the advantages of low cost and good heat resistance and stability. After being spray-dried and coated with graphene oxide, a multi-fold structure is formed on the surface, which avoids the agglomeration between quantum dots and graphene oxide-coated ZnCNi3, increases the specific surface area, further improves the efficiency of blocking ultraviolet and blue light, and has better temperature resistance.
[0028] The present invention prepares a quantum dot color conversion film, which has good resistance to high blue light radiation and high temperature, high efficiency in blocking ultraviolet light and blue light, low cost, good heat resistance and chemical resistance, can withstand water and oxygen environments, and has broad application prospects. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] This embodiment provides a method for preparing a quantum dot color conversion film that is resistant to high blue light radiation and high temperature, comprising the following steps:
[0032] S1. Preparation of Zn-In / La-S quantum dots: 0.3 g zinc acetate, 0.5 g indium acetate, 0.2 g lanthanum acetate, 0.6 g sulfur powder, 40 g oleylamine, and 30 g mercaptan were mixed, heated to 220°C under nitrogen protection, reacted for 10 min, and cooled to room temperature to obtain a Zn-In / La-S quantum dot reaction solution;
[0033] S2. Coating ZnS shell: 0.7 g zinc acetate was dissolved in 10 g oleylamine and octadecene solution, added to 100 g Zn-In / La-S quantum dot reaction solution described in step S1, heated to 240 ° C, reacted for 20 min, cooled to room temperature, purified by methanol 3 times, centrifuged to obtain Zn-In / La-S quantum dots coated with ZnS shell;
[0034] S3. Polydopamine coating: 1 g Zn-In / La-S quantum dots coated with ZnS shell was added to 50 mL water, 0.2 g dopamine hydrochloride and 0.01 g catalyst were added, heated to 35 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain modified Zn-In / La-S quantum dots coated with ZnS shell;
[0035] A Tris-HCl solution of the catalyst with a pH of 8.5;
[0036] S4. Preparation of ZnCNi3: 1 mmol ZnO and 2 mmol NiO were mixed, 4 mmol melamine was added, the mixture was stirred for 15 min, and calcined at 550 °C for 10 h to obtain ZnCNi3;
[0037] S5. Graphene oxide coating: 0.3 g of graphene oxide was added to 50 mL of water, 1 g of ZnCNi3 was added, ultrasonically dispersed at 1000 W for 15 min, and spray dried to obtain graphene oxide-coated ZnCNi3;
[0038] S6. Preparation of suspension: 0.7 g of modified Zn-In / La-S quantum dots coated with ZnS shell and 0.3 g of graphene oxide coated ZnCNi3 were added to 10 mL of n-octane and stirred for 15 min to obtain a suspension;
[0039] S7. Preparation of quantum dot color conversion film resistant to high blue light radiation and high temperature: spin coat the suspension at 2500r / min for 40s on a polycarbonate film, treat the other side in the same way, and dry to obtain a quantum dot color conversion film resistant to high blue light radiation and high temperature.
[0040] Example 2
[0041] This embodiment provides a method for preparing a quantum dot color conversion film that is resistant to high blue light radiation and high temperature, comprising the following steps:
[0042] S1. Preparation of Zn-In / La-S quantum dots: 0.4 g zinc acetate, 0.7 g indium acetate, 0.3 g lanthanum acetate, 0.8 g sulfur powder, 70 g oleylamine, and 50 g mercaptan were mixed, heated to 240°C under nitrogen protection, reacted for 15 min, and cooled to room temperature to obtain a Zn-In / La-S quantum dot reaction solution;
[0043] S2. Coating ZnS shell: 1 g of zinc acetate was dissolved in 10 g of oleylamine and octadecene solution, added to 120 g of the Zn-In / La-S quantum dot reaction solution described in step S1, heated to 250 ° C, reacted for 30 min, cooled to room temperature, purified by methanol 3 times, centrifuged, and obtained Zn-In / La-S quantum dots coated with ZnS shell;
[0044] S3. Polydopamine coating: 1 g Zn-In / La-S quantum dots coated with ZnS shell was added to 50 mL of water, 0.3 g dopamine hydrochloride and 0.02 g catalyst were added, heated to 45 ° C, stirred for 5 h, centrifuged, washed, and dried to obtain modified Zn-In / La-S quantum dots coated with ZnS shell;
[0045] The catalyst has a pH of 9.5 in a Tris-HCl solution;
[0046] S4. Preparation of ZnCNi3: 1 mmol ZnO and 4 mmol NiO were mixed, 6 mmol melamine was added, the mixture was stirred for 15 min, and calcined at 650 °C for 14 h to obtain ZnCNi3;
[0047] S5. Graphene oxide coating: 0.5 g of graphene oxide was added to 50 mL of water, 1 g of ZnCNi3 was added, ultrasonically dispersed at 1000 W for 15 min, and spray dried to obtain graphene oxide-coated ZnCNi3;
[0048] S6. Preparation of suspension: 1 g of modified Zn-In / La-S quantum dots coated with ZnS shell and 0.5 g of graphene oxide coated ZnCNi3 were added to 20 mL of n-octane and stirred for 15 min to obtain a suspension;
[0049] S7. Preparation of quantum dot color conversion film resistant to high blue light radiation and high temperature: spin coat the suspension at 3500r / min for 50s on a polycarbonate film, treat the other side in the same way, and dry to obtain a quantum dot color conversion film resistant to high blue light radiation and high temperature.
[0050] Example 3
[0051] This embodiment provides a method for preparing a quantum dot color conversion film that is resistant to high blue light radiation and high temperature, comprising the following steps:
[0052] S1. Preparation of Zn-In / La-S quantum dots: 0.37 g zinc acetate, 0.6 g indium acetate, 0.24 g lanthanum acetate, 0.7 g sulfur powder, 50 g oleylamine, and 40 g mercaptan were mixed, heated to 230°C under nitrogen protection, reacted for 12 min, and cooled to room temperature to obtain a Zn-In / La-S quantum dot reaction solution;
[0053] S2. Coating ZnS shell: 0.8 g zinc acetate was dissolved in 10 g oleylamine and octadecene solution, added to 110 g Zn-In / La-S quantum dot reaction solution described in step S1, heated to 245 ° C, reacted for 25 min, cooled to room temperature, purified by methanol 3 times, centrifuged, and obtained Zn-In / La-S quantum dots coated with ZnS shell;
[0054] S3. Polydopamine coating: 1 g Zn-In / La-S quantum dots coated with ZnS shell was added to 50 mL water, 0.25 g dopamine hydrochloride and 0.015 g catalyst were added, heated to 40 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain modified Zn-In / La-S quantum dots coated with ZnS shell;
[0055] A Tris-HCl solution of the catalyst with a pH of 9;
[0056] S4. Preparation of ZnCNi3: 1 mmol ZnO and 3 mmol NiO were mixed, 5 mmol melamine was added, the mixture was stirred for 15 min, and calcined at 600 °C for 12 h to obtain ZnCNi3;
[0057] S5. Graphene oxide coating: 0.4 g of graphene oxide was added to 50 mL of water, 1 g of ZnCNi3 was added, ultrasonically dispersed at 1000 W for 15 min, and spray dried to obtain graphene oxide-coated ZnCNi3;
[0058] S6. Preparation of suspension: 0.85 g of modified Zn-In / La-S quantum dots coated with ZnS shell and 0.4 g of graphene oxide coated ZnCNi3 were added to 15 mL of n-octane and stirred for 15 min to obtain a suspension;
[0059] S7. Preparation of quantum dot color conversion film resistant to high blue light radiation and high temperature: spin coat the suspension at 3000r / min for 45s on a polycarbonate film, treat the other side in the same way, and dry to obtain a quantum dot color conversion film resistant to high blue light radiation and high temperature.
[0060] Comparative Example 1
[0061] Compared with Example 3, the difference is that indium acetate is not added in step S1.
[0062] The details are as follows:
[0063] S1. Preparation of Zn-La-S quantum dots: 0.37 g zinc acetate, 84 g lanthanum acetate, 0.7 g sulfur powder, 50 g oleylamine and 40 g thiol were mixed, heated to 230°C under nitrogen protection, reacted for 12 min, and cooled to room temperature to obtain a Zn-La-S quantum dot reaction solution.
[0064] Comparative Example 2
[0065] Compared with Example 3, the difference is that lanthanum acetate is not added in step S1.
[0066] The details are as follows:
[0067] S1. Preparation of Zn-In-S quantum dots: 0.37 g zinc acetate, 0.84 g indium acetate, 0.7 g sulfur powder, 50 g oleylamine and 40 g thiol were mixed, heated to 230 °C under nitrogen protection, reacted for 12 min, and cooled to room temperature to obtain a Zn-In-S quantum dot reaction solution.
[0068] Comparative Example 3
[0069] Compared with Example 3, the difference is that indium acetate and lanthanum acetate are not added in step S1.
[0070] The details are as follows:
[0071] S1. Preparation of ZnS quantum dots: 0.37 g zinc acetate, 0.7 g sulfur powder, 50 g oleylamine and 40 g thiol were mixed, heated to 230°C under nitrogen protection, reacted for 12 min, and cooled to room temperature to obtain a ZnS quantum dot reaction solution.
[0072] Comparative Example 4
[0073] Compared with Example 3, the difference is that step S2 is not performed.
[0074] The details are as follows:
[0075] S1. Preparation of Zn-In / La-S quantum dots: 0.37 g zinc acetate, 0.6 g indium acetate, 0.24 g lanthanum acetate, 0.7 g sulfur powder, 50 g oleylamine, and 40 g mercaptan were mixed, heated to 230°C under nitrogen protection, reacted for 12 min, cooled to room temperature, centrifuged, washed, and freeze-dried to obtain Zn-In / La-S quantum dots;
[0076] S2. Polydopamine coating: 1 g Zn-In / La-S quantum dots were added to 50 mL water, 0.25 g dopamine hydrochloride and 0.015 g catalyst were added, heated to 40 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain modified Zn-In / La-S quantum dots;
[0077] A Tris-HCl solution of the catalyst with a pH of 9;
[0078] S3. Preparation of ZnCNi3: 1 mmol ZnO and 3 mmol NiO were mixed, 5 mmol melamine was added, the mixture was stirred for 15 min, and calcined at 600 °C for 12 h to obtain ZnCNi3;
[0079] S4. Graphene oxide coating: 0.4 g of graphene oxide was added to 50 mL of water, 1 g of ZnCNi3 was added, ultrasonically dispersed at 1000 W for 15 min, and spray dried to obtain graphene oxide-coated ZnCNi3;
[0080] S5. Preparation of suspension: 0.85 g of modified Zn-In / La-S quantum dots and 0.4 g of graphene oxide-coated ZnCNi3 were added to 15 mL of n-octane and stirred for 15 min to obtain a suspension;
[0081] S6. Preparation of quantum dot color conversion film resistant to high blue light radiation and high temperature: spin coat the suspension at 3000r / min for 45s on a polycarbonate film, treat the other side in the same way, and dry to obtain a quantum dot color conversion film resistant to high blue light radiation and high temperature.
[0082] Comparative Example 5
[0083] Compared with Example 3, the difference is that step S3 is not performed.
[0084] The details are as follows:
[0085] S1. Preparation of Zn-In / La-S quantum dots: 0.37 g zinc acetate, 0.6 g indium acetate, 0.24 g lanthanum acetate, 0.7 g sulfur powder, 50 g oleylamine, and 40 g mercaptan were mixed, heated to 230°C under nitrogen protection, reacted for 12 min, and cooled to room temperature to obtain a Zn-In / La-S quantum dot reaction solution;
[0086] S2. Coating ZnS shell: 0.8 g zinc acetate was dissolved in 10 g oleylamine and octadecene solution, added to 110 g Zn-In / La-S quantum dot reaction solution described in step S1, heated to 245 ° C, reacted for 25 min, cooled to room temperature, purified by methanol 3 times, centrifuged, and obtained Zn-In / La-S quantum dots coated with ZnS shell;
[0087] S3. Preparation of ZnCNi3: 1 mmol ZnO and 3 mmol NiO were mixed, 5 mmol melamine was added, the mixture was stirred for 15 min, and calcined at 600 °C for 12 h to obtain ZnCNi3;
[0088] S4. Graphene oxide coating: 0.4 g of graphene oxide was added to 50 mL of water, 1 g of ZnCNi3 was added, ultrasonically dispersed at 1000 W for 15 min, and spray dried to obtain graphene oxide-coated ZnCNi3;
[0089] S5. Preparation of suspension: 0.85 g of Zn-In / La-S quantum dots coated with ZnS shell and 0.4 g of graphene oxide coated ZnCNi3 were added to 15 mL of n-octane and stirred for 15 min to obtain a suspension;
[0090] S6. Preparation of quantum dot color conversion film resistant to high blue light radiation and high temperature: spin coat the suspension at 3000r / min for 45s on a polycarbonate film, treat the other side in the same way, and dry to obtain a quantum dot color conversion film resistant to high blue light radiation and high temperature.
[0091] Comparative Example 6
[0092] Compared with Embodiment 3, the difference is that step S5 is not performed.
[0093] The details are as follows:
[0094] S1. Preparation of Zn-In / La-S quantum dots: 0.37 g zinc acetate, 0.6 g indium acetate, 0.24 g lanthanum acetate, 0.7 g sulfur powder, 50 g oleylamine, and 40 g mercaptan were mixed, heated to 230°C under nitrogen protection, reacted for 12 min, and cooled to room temperature to obtain a Zn-In / La-S quantum dot reaction solution;
[0095] S2. Coating ZnS shell: 0.8 g zinc acetate was dissolved in 10 g oleylamine and octadecene solution, added to 110 g Zn-In / La-S quantum dot reaction solution described in step S1, heated to 245 ° C, reacted for 25 min, cooled to room temperature, purified by methanol 3 times, centrifuged, and obtained Zn-In / La-S quantum dots coated with ZnS shell;
[0096] S3. Polydopamine coating: 1 g Zn-In / La-S quantum dots coated with ZnS shell was added to 50 mL water, 0.25 g dopamine hydrochloride and 0.015 g catalyst were added, heated to 40 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain modified Zn-In / La-S quantum dots coated with ZnS shell;
[0097] A Tris-HCl solution of the catalyst with a pH of 9;
[0098] S4. Preparation of ZnCNi3: 1 mmol ZnO and 3 mmol NiO were mixed, 5 mmol melamine was added, the mixture was stirred for 15 min, and calcined at 600 °C for 12 h to obtain ZnCNi3;
[0099] S5. Preparation of suspension: 0.85 g of modified Zn-In / La-S quantum dots coated with ZnS shell and 0.4 g of ZnCNi3 were added to 15 mL of n-octane and stirred for 15 min to obtain a suspension;
[0100] S6. Preparation of quantum dot color conversion film resistant to high blue light radiation and high temperature: spin coat the suspension at 3000r / min for 45s on a polycarbonate film, treat the other side in the same way, and dry to obtain a quantum dot color conversion film resistant to high blue light radiation and high temperature.
[0101] Comparative Example 7
[0102] Compared with Example 3, the difference is that graphene oxide-coated ZnCNi3 is not added in step S6.
[0103] The details are as follows:
[0104] S6. Preparation of suspension: 1.25 g of modified Zn-In / La-S quantum dots coated with ZnS shells were added to 15 mL of n-octane and stirred for 15 minutes to obtain a suspension.
[0105] Test Example 1
[0106] The quantum dot color conversion films resistant to high blue light radiation and high temperature prepared in Examples 1-3 and Comparative Examples 1-7 were assembled into a structure, which includes, from top to bottom: a PET covering film, an adhesive layer (thickness 21.4 μm), a quantum dot color conversion film resistant to high blue light radiation and high temperature prepared in Examples 1-3 or Comparative Examples 1-7, and a base PET film. Performance tests were performed, and the results are shown in Table 1.
[0107] (1) Haze measurement
[0108] The turbidity of the film is measured using the HM-150 device. The light emitted from the lamp penetrates the sample and is incident into the integrating sphere. In this case, the light is divided into diffuse light (DT) and parallel light (PT) by the sample, and these lights are reflected in the integrating sphere and then gathered in the light receiving device. The gathered light is transferred to the measuring section, and the required measurement data is output to the display.
[0109] (2) Measurement of brightness and quantum yield (QY)
[0110] The brightness and quantum yield of the prepared quantum dot color conversion film resistant to high blue light radiation and high temperature are calculated by measuring the brightness spectrum using a spectroradiometer. The light guide plate of the backlight unit including a red LED (maximum emission wavelength of 620nm) and a light guide plate is stacked on one surface of the prepared quantum dot color conversion film resistant to high blue light radiation and high temperature, and the prism sheet and the dual brightness enhancement film (DBEF) are stacked on the other surface of the quantum dot color conversion film resistant to high blue light radiation and high temperature, and then the brightness spectrum of the film is measured. The initial value is set so that when the brightness spectrum is measured, the brightness of the red LED lamp is 600 nits in the absence of the quantum dot color conversion film resistant to high blue light radiation and high temperature.
[0111] Table 1
[0112]
[0113] It can be seen from the above table that the quantum dot color conversion films resistant to high blue light radiation and high temperature prepared in Examples 1-3 of the present invention have high brightness and quantum yield.
[0114] Test Example 2
[0115] The quantum dot color conversion film resistant to high blue light radiation and high temperature prepared in Examples 1-3 and Comparative Examples 1-7 was assembled into a structure, which is composed of the following from top to bottom: PET covering film, adhesive layer (thickness 21.4 μm), quantum dot color conversion film resistant to high blue light radiation and high temperature prepared in Examples 1-3 or Comparative Examples 1-7, and base PET film, and the performance test was performed. The light guide plate of the backlight unit including dual blue light wavelength LED (blue light wavelength is 440nm, blue-violet wavelength is 500nm) and light guide plate was stacked on one surface of the prepared quantum dot color conversion film resistant to high blue light radiation and high temperature, and the prism sheet and dual brightness enhancement film (DBEF) were stacked on the other surface of the quantum dot color conversion film resistant to high blue light radiation and high temperature, and then the brightness spectrum of the film was measured. The emission intensity of the blue light peak when the test current was 40mA. The initial value was set so that when measuring the brightness spectrum, the ratio of the emission intensity of the blue light peak and the blue-violet light peak of the LED lamp was 4.45 in the absence of a quantum dot color conversion film that is resistant to high blue light radiation and high temperature. The results are shown in Table 2.
[0116] Table 2
[0117] Group The ratio of the emission intensity of the blue light peak and the blue-violet light peak Example 1 0.87 Example 2 0.85 Example 3 0.82 Comparative Example 1 2.42 Comparative Example 2 1.17 Comparative Example 3 2.98 Comparative Example 4 1.85 Comparative Example 5 1.08 Comparative Example 6 1.98 Comparative Example 7 2.27
[0118] It can be seen from the above table that the quantum dot color conversion films resistant to high blue light radiation and high temperature prepared in Examples 1-3 of the present invention have good blue light blocking effects.
[0119] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a quantum dot color conversion film resistant to high blue light radiation and high temperature, characterized in that: Zn-In / La-S quantum dots were prepared, and after a ZnS shell was grown on the surface, a layer of polydopamine was coated to obtain modified Zn-In / La-S quantum dots coated with a ZnS shell, which were mixed with graphene oxide-coated ZnCNi3 in a solvent and evenly spin-coated on a polycarbonate film. The other side was treated in the same way and dried to obtain a quantum dot color conversion film that was resistant to high blue light radiation and high temperature.
2. The preparation method according to claim 1, characterized in that: The following steps are involved: S1. Preparation of Zn-In / La-S quantum dots: zinc acetate, indium acetate, lanthanum acetate, sulfur powder, oleylamine and thiol were mixed, heated for reaction under the protection of inert gas, and cooled to room temperature to obtain a Zn-In / La-S quantum dot reaction solution; S2. Coating with ZnS shell: dissolving zinc acetate in oleylamine and octadecene solution, adding to the Zn-In / La-S quantum dot reaction solution in step S1, heating the reaction, cooling to room temperature, purifying with methanol, centrifuging, and obtaining Zn-In / La-S quantum dots coated with ZnS shell; S3. Polydopamine coated layer: Add Zn-In / La-S quantum dots coated with ZnS shell into water, add dopamine hydrochloride and catalyst, heat and stir to react, centrifuge, wash, and dry to obtain modified Zn-In / La-S quantum dots coated with ZnS shell; S4. Preparation of ZnCNi3: ZnO and NiO are mixed, melamine is added, stirred and mixed evenly, and calcined to obtain ZnCNi3; S5. Graphene oxide coating: adding graphene oxide to water, adding ZnCNi3, ultrasonically dispersing uniformly, spray drying, to obtain graphene oxide coated ZnCNi3; S6. Preparation of the suspension: The modified Zn-In / La-S quantum dots coated with ZnS shell and graphene oxide coated ZnCNi3 were added to the solvent and stirred to mix well to obtain a suspension; S7. Preparation of quantum dot color conversion film resistant to high blue light radiation and high temperature: evenly spin-coat the suspension on a polycarbonate film, treat the other side in the same way, and dry to obtain a quantum dot color conversion film resistant to high blue light radiation and high temperature.
3. The preparation method according to claim 2, characterized in that: In step S1, the mass ratio of zinc acetate, indium acetate, lanthanum acetate, sulfur powder, oleylamine and mercaptan is 3-4:5-7:2-3:6-8:400-700:300-500, the temperature of the heating reaction is 220-240° C., and the time is 10-15 min.
4. The preparation method according to claim 2, characterized in that: The mass ratio of zinc acetate, oleylamine and octadecene solution to Zn-In / La-S quantum dot reaction solution in step S2 is 7-10:100:1000-1200, the temperature of the heating reaction is 240-250°C, and the time is 20-30min.
5. The preparation method according to claim 2, characterized in that: In step S3, the mass ratio of the Zn-In / La-S quantum dots coated with the ZnS shell, dopamine hydrochloride and the catalyst is 10:2-3:0.1-0.2, the pH of the catalyst is a Tris-HCl solution of 8.5-9.5, the temperature of the heating and stirring reaction is 35-45°C, and the time is 3-5h.
6. The preparation method according to claim 2, characterized in that: In step S4, the molar ratio of ZnO, NiO and melamine is 1:2-4:4-6, the calcination temperature is 550-650° C., and the calcination time is 10-14 hours.
7. The preparation method according to claim 2, characterized in that: The mass ratio of graphene oxide to ZnCNi3 in step S5 is 3-5:
10.
8. The preparation method according to claim 2, characterized in that: The mass ratio of the modified Zn-In / La-S quantum dots coated with ZnS shells, graphene oxide coated ZnCNi3 and the solvent in step S6 is 7-10:3-5:100-200, and the solvent is at least one of n-octane, n-hexane, cyclohexane and petroleum ether.
9. The preparation method according to claim 2, characterized in that: The spin coating in step S7 has a rotation speed of 2500-3500 r / min and a time of 40-50 s.
10. A quantum dot color conversion film resistant to high blue light radiation and high temperature, prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Quantum dot ink based on ink-jet printing
CN109321038A
Efficient fluorescent material based on quantum dot-aggregation-induced emission molecules
CN110894424A
Light-emitting device, light-emitting apparatus, electronic device, display device, and lighting device
CN113412438A
Perovskite quantum dot material with gas-sensitive property and application thereof
CN114540024A
Quantum dot film material with gas-sensitive property and application thereof
CN114933758A